PENGARUH BIAYA PRODUKSI, LEVERAGE, PERTUMBUHAN PENJUALAN DAN PERPUTARAN PERSEDIAAN TERHADAP LABA BERSIH PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA 2020-2024 - Tegar Dwi Wantoro; Ernawati Malik (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to examine the effect of production costs, leverage, sales growth, and inventory turnover on net profit in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange during the 2020–2024 period. This research employs a quantitative approach. The population consists of 95 manufacturing companies in the food and beverage sub-sector, with a sample of 17 companies. The data collection method used is documentation. The data analysis method is multiple linear regression analysis using SPSS version 22. The results of this study indicate that partially (t-test), production costs and inventory turnover have a significant effect on net profit in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange during the 2020–2024 period, while leverage and sales growth do not have a significant effect on net profit in manufacturing companies in the food and beverage sub-sector. Based on the simultaneous test results (F-test), production costs, leverage, sales growth, and inventory turnover simultaneously have a significant effect on net profit in manufacturing companies in the food and beverage sub-sector.